Tamburlaine, Parts I and II : Doctor Faustus, A- and B-Texts : The Jew of Malta : Edward II - Marlowe, Christopher 1564-1593; Edited by David Bevington and Eric Rasmussen (Oxford, New York Oxford University Press, 1998)
This edition offers Marlowe's five major plays, which show the radicalism and vitality of his writing in the few years before his violent death. The texts of the plays have been edited and are presented with modernized spelling and punctuation. There is a scholarly introduction and annotation.
Include Bibliography and Glossary
Keywords: Faust, -approximately 1540 -- Magicians -- Germany -- Timur, 1336-1405 -- Edward II, King of England, 1284-1327